Analyzing Quality of Water in River using IoT - Poonam J Chavan,; Manoj A Mechkul, (Journal of Power Electronics and Devices, 2016)
Internet of Things (IoT) is international network of “smart device” which will sense and interrelate with their atmosphere mistreatment the net for his or her communication and interaction with users and different systems. The main conception behind every IoT technology and implementation is “Device is integrated with the virtual world of internet and interacts with it by following, sensing and monitoring object and their environment”. The structures of a “smart device” that may act as a member of IoT network are, collect and transmit knowledge, actuate device supported activates and receive info (from network and internet). Presently in our country, the water analysis is completed manually by taking the samples from the water sources (river) and send to the research lab for study. To mechanize this method, water quality watching sensors, ARM7, are physically placed in each and every water sources (river). The water quality watching sensors gather knowledge from water. The ARM7 forward that knowledge to concentrator module through Wi-Fi module for remote transfer of information to the research lab. The information concentrator that is found in each and every lake, send that knowledge to the cloud organized server that is settled within the testing laboratory. The department workers monitor this data remotely and securely provide this data to the requested users which are stored in the cloud.